The Impact of Integrated Support and Context on Treatment Implementation and Child Outcomes Following Behavioral Consultation. Issue 6 (November 2022) - Noell, George; Gansle, Kristin; Gulley, Veronica
Assuring treatment plan implementation following consultation is critically important because implementation is strongly related to outcomes. Treatment implementation has been hypothesized to be influenced by both the nature of the follow-up support provided and contextual variables. However, studies to date have not examined both issues while directly measuring implementation. This study examined treatment implementation following consultation for 48 teachers in public schools who had referred a student for intervention services in a randomized clinical field trial. Participating teachers in the experimental group received Integrated Support (IS). IS includes social influence, planning, and performance feedback elements. IS was compared to weekly follow-up meetings alone. Treatment implementation and child outcomes were markedly superior for IS as compared to weekly follow-up. Three school climate factors were found to be correlated with treatment implementation for the IS group, but not the weekly follow-up group. Participants rated treatment implementation, treatment acceptability, and consultant effectiveness positively and similarly across conditions. The implications of these findings for future work examining school culture, consultation and intervention are discussed.